La pensée politique du dernier Camus - Jean‑Baptiste Dussert (Carnets)
Throughout his literary career, Albert Camus was the victim of a certain condescension on the part of "professional" philosophers. This led to his famous break with Jean-Paul Sartre. This article examines the political isolation of the author of The Rebel in the last years of his life and imagine how he would have reacted to the independence of Algeria.